Analisis Wacana Persuasif Pada Buku "Awas!!! Bahaya Kanker Payudara Dan Kanker Serviks" Karya Dra. Ch. Erni Kartikawati, M.Pd. - Sutarno, Ayu Lestari (2016)
The objectives of this research were: 1) To describe the language characteristics used in the persuasive discourse in the book buku "Awas!!! Bahaya Kanker Payudara dan Kanker Serviks". 2) To identify the message contents containing in the persuasive discourse in the book "Awas!!! Bahaya Kanker Payudara dan Kanker Serviks". This research is a qualitative research. The data source in this research were written data taken from the book "Awas!!! Bahaya Kanker Payudara dan Kanker Serviks". The methods of data collection used were the documentation method and the method of observing and taking a note.The techniques of data analysis used the identity method (metode padan) and the distributional method (metode agih). Based on the results of the research written in the chapter IV in this research, the researcher could conclude that 1) The language characteristics used in the persuasive discourse in the book of this research which were found were: (1) the use of foreign language; (2) words of diseases; names; and (3) words of body organs' names; 2) The message contents containing in the persuasive discourse were in the forms of advice, self-confidence, suggestion, order, information, confirmation, and recommendation.